Preparation of recombinant coat protein of Prunus necrotic ringspot virus - Petrzik, K; Mráz, I; Kubelková, D (Acta virologica, 2001)
The coat protein (CP) gene of Prunus necrotic ringspot virus (PNRSV) was cloned into pET 16b vector and expressed in Escherichia coli. CP-enriched fractions were prepared from whole cell lysate by differential centrifugation. The fraction sedimenting at 20,000 x g for 30 mins was used for preparation of a rabbit antiserum to CP. This antiserum had a titer of 1:2048 and reacted in a double-antibody sandwich ELISA (DAS-ELISA).
Keywords: kapsida; stromy; Base Sequence; klonování DNA; Ilarvirus; Molecular Sequence Data; rekombinantní proteiny; molekulární sekvence - údaje; Recombinant Proteins; Trees; Cloning, Molecular; Capsid; Genes, Viral; sekvence nukleotidů; virové geny